2016
DOI: 10.1007/s00520-016-3149-7
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative evaluation of a group phone-based weight loss intervention for rural breast cancer survivors: Themes and mechanisms of success

Abstract: Purpose Obesity is prevalent in breast cancer survivors and is a significant risk factor for recurrence and mortality. Weight management interventions for survivors have been diverse in design (in-person vs. phone-based, group vs. individual) and yielded varying weight loss results. Given these issues, participants themselves may provide insight into treatment-based factors that contributed to their weight loss outcomes. Here we report qualitative results from interviews with survivors in a group phone-based w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 44 publications
0
50
0
Order By: Relevance
“…The study demonstrated feasibility and achieved a 12.9% weight loss—with a 10.6% net loss maintained at 18 months—through continued, but scaled back, conference calls. Lessons learned from that study are needs for: 1) direct patient recruitment through cancer registries (direct mailing yielded 84% of participants, whereas physician referrals yielded only 4%); 2) clinical integration (because of high levels of comorbid conditions); and 3) group support among rural women . While the intervention was exclusively home based, many participants arranged to meet in person with one another; therefore, some face‐to‐face contact may enhance intervention efficacy for some and needs to be considered in future programming.…”
Section: Effective Approaches For Improving Weight Management and Pamentioning
confidence: 99%
“…The study demonstrated feasibility and achieved a 12.9% weight loss—with a 10.6% net loss maintained at 18 months—through continued, but scaled back, conference calls. Lessons learned from that study are needs for: 1) direct patient recruitment through cancer registries (direct mailing yielded 84% of participants, whereas physician referrals yielded only 4%); 2) clinical integration (because of high levels of comorbid conditions); and 3) group support among rural women . While the intervention was exclusively home based, many participants arranged to meet in person with one another; therefore, some face‐to‐face contact may enhance intervention efficacy for some and needs to be considered in future programming.…”
Section: Effective Approaches For Improving Weight Management and Pamentioning
confidence: 99%
“…Novel strategies are needed to improve adherence to physical activity recommendations in non-supervised settings, where the broadest population impact is likely to occur ( 29 ). Our previous qualitative findings indicated that participants appeared to underestimate the impact of environmental barriers on their physical activity, which may be a point of focus for future interventions ( 30 ). In a recent pilot study examining tailored text messages for promoting weight loss maintenance, Spark et al found a drop in physical activity from 6 to 12 months, but a return to 6 month physical activity levels by 18 months ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Articles generally did not provide a detailed discussion of the ways in which the intervention had been tailored for a rural target population. For those that did, information typically included a discussion of how a given intervention held potential for addressing the needs of under‐resourced areas and barriers specific to rural communities (eg, “Our findings also indicate that group facilitation via phone is a potential approach for reaching geographically dispersed, rural [breast cancer] survivors, and that phone‐based group facilitation appears to cultivate the same important group mechanisms as in‐person groups, such as peer accountability, information exchange, and support.”) and to provide examples of adaptations (eg, “There are no large public exercise or pool facilities in Miles City. The lifestyle coaches through creative community partnerships identified resources to provide the required physical activity sessions.…”
Section: Resultsmentioning
confidence: 99%
“…For those that did, information typically included a discussion of how a given intervention held potential for addressing the needs of under-resourced areas and barriers specific to rural communities (eg, "Our findings also indicate that group facilitation via phone is a potential approach for reaching geographically dispersed, rural [breast cancer] survivors, and that phone-based group facilitation appears to cultivate the same important group mechanisms as in-person groups, such as peer accountability, information exchange, and support." 48 facility." 37 ).…”
Section: (20%)mentioning
confidence: 99%